Manage India - The Strategic Management of Corporate and Social Sector - Sarin, Anil (Prabandhan: Indian Journal of Management, 2010)
Amazingly, the economists, corporate players who used to make predictions about the economy or the growth of the corporate sector even for 2025, 2050…. were not able to foresee the monster of recession even few months in advance. Before the recession, economists, corporate players were talking about the requirement of the manpower paucity in future for matching the economical growth. Amazingly, professionals made liberal predictions of economy and manpower requirement in 2015, 2020, 2030, 2050….but there was no serious prediction about the millions of people losing the jobs in next few months. Till the start of 2008, when overall world economy was doing better and corporate sector was growing by leaps and bounds, nobody predicted that in just few months, the economy would be crippled and a country like USA would be sucked in the black hole of recession. Interestingly, decision makers, and economists are considered experts in giving direction to the overall economical growth, but on many occasions, and this time around also, they failed miserably in steering the economy on the slippery road of recession. The monster of deflation came out of its old grave and caught these so called future economic/business predictors unaware about this new development. The recent economic crisis has put a big question mark on the worthiness of the existing economical models/concepts and also on the vision and the capabilities of so called economists and the decision makers of both government and corporate sector. India is so vast and diverse that the impact of difficult times varied from state to state, city to city, town to town, village to village. The Indian corporate sector, people, economists and government were far more worried about the impact of the global recession than of the unfortunate Mumbai and Pune attacks. The severe effects of the slowdown did not harm much as more than 60 percent of the population in India is engaged directly or indirectly with the agriculture sector, which is intensively and extensively labor oriented and highly socialized. More than 80 percent of Indian families depending on agriculture are in rural areas with moderate exposure to the products manufactured and marketed by the corporate sector. Being part of the bottom of the pyramid, this segment has been explored till now by few corporate organizations only. These organizations are satisfying hardly few needs of this low income segment through their products (normally low price with optimum quality) which is unevenly spread geographically throughout the country. In fact, the products of cottage industry and unorganized local traditional industry have penetrated the Indian rural market deeply.